The setbacks of the political and mediagenic scandal in the brazilian 2014 presidential elections - Fernandes, Carla Montuori (2015)
The political scandal in contemporary democracyis linked to the concepts of transgression andmediatization. The act of breaking rules legallyprotected or systems of values of a society andthe reporting of public events in the global levelconsolidate the basis of the political and mediagenicscandal. In the Brazilian 2014 presidentialelections, allegations of a corruption schemeinvolving Petrobras mobilized political actors, especiallyPresident Dilma Rousseff (PT), who disputedthe second presidential term. Therefore, thepaper aims to study the framework of the politicalscandal of Petrobras in the Jornal Nacional newsprogram during the election campaign.